2012
DOI: 10.1111/j.1750-2659.2012.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Review on the impact of pregnancy and obesity on influenza virus infection

Abstract: Please cite this paper as: Karlsson et al. (2012) Review on the impact of pregnancy and obesity on influenza virus infection. Influenza and Other Respiratory Viruses 6(6), 449–460.A myriad of risk factors have been linked to an increase in the severity of the pandemic H1N1 2009 influenza A virus [A(H1N1)pdm09] including pregnancy and obesity where death rates can be elevated as compared to the general population. The goal of this review is to provide an overview of the influence of pregnancy and obesity on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 167 publications
(200 reference statements)
1
34
1
Order By: Relevance
“…The link between obesity and influenza was first recorded in the early stage of the pandemic in 2009, when the data from numerous countries indicated that obese people were at higher risk of hospitalization, ICU admission, and developing more severe forms of the disease (13,14). Obese patients with and without chronic diseases were at increased risk of respiratory complications during the influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…The link between obesity and influenza was first recorded in the early stage of the pandemic in 2009, when the data from numerous countries indicated that obese people were at higher risk of hospitalization, ICU admission, and developing more severe forms of the disease (13,14). Obese patients with and without chronic diseases were at increased risk of respiratory complications during the influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Obesity has recently been identified as an independent risk factor, and pregnancy has long been associated with increased risk. 10,11 Complications of influenza, including hemorrhagic bronchitis, diffuse Q3 alveolar damage, and pneumonia, can develop within hours. Fulminant fatal influenza viral pneumonia occasionally occurs, but most pneumonias are caused by secondary bacterial infections.…”
Section: Q2mentioning
confidence: 99%
“…Among women of low socioeconomic status, rates of clinically significant depressive symptoms may be as high as 47-52% [68, 69]. Due to substantial pregnancy-related immune changes, pregnant women may be more susceptible than non-pregnant adults to stress-induced immune dysregulation [70, 71]. However, despite their high risk status for influenza complications, the literature lacks information on effects of psychological factors on antibody responses following influenza vaccination in pregnant women.…”
Section: Potential Behavioral Risk Factors For Poor Antibody Respomentioning
confidence: 99%